ROOF AND SIDE WALL SHINGLES FROM COCONUT PALM WOOD - V.K. Sulc (International Coconut Community Journal, 1990)
In a number of coconut palm growing countries, thatched roofs made from indigenous materials such as palm leaves and from suitable tropical grasses such as Imperata cylindirca L. (Cogon) are traditionally used. The most suitable and durable among the palms appear to be the mature leaves of nipa palm. Depending on the quality of leaves and thickness of layers, the serviceable life span of thatched roof is approximalely 5 to 8 years, coconut palm leaves are one of the poorest materials for roofing of permanent dwelling. They easily become brittle when dry and break into bits during rain and wind.